Polymer latex with core-shell structure as well as preparation method and application of polymer latex
Through seed emulsion polymerization technology, the addition rate and proportion of seed emulsion monomers are controlled, combined with appropriate surfactants and initiators, core-shell structure polymer latex with uniform particle size distribution and excellent performance are prepared, solving the existing solutions Problems of difficulty in controlling latex particle size in technology.
Patent Information
- Application Number
- CN202311024243.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, when preparing polymer latex with core-shell structures, it is difficult to effectively control the particle size and distribution of latex particles, affecting its mechanical properties and stability.
Through seed emulsion polymerization technology, the addition rate and proportion of seed emulsion monomers are controlled, and combined with appropriate surfactants and initiators are used to gradually form polymer latex with core-shell structure.
The preparation of core-shell structure polymer latex with high conversion rate is achieved, with uniform particle size distribution, low viscosity, and good processing performance, heat and oil resistance.
Smart Images

Figure BDA0004394907400000201
Abstract
Description
Technical Field
[0001] The invention relates to the field of latex, and in particular to a polymer latex with a core-shell structure prepared by using seed emulsion polymerization technology, and a preparation method and application thereof. Background Art
[0002] Core-shell polymers, also known as core-shell polymers, are one of the products of emulsion polymerization. They refer to particulate polymers in which the core and shell are respectively composed of two or more polymer-enriched layers. Graft copolymer products are often formed between the core and shell.
[0003] The seed emulsion is made in a seed kettle. The process is as follows: first, water, emulsifier, water-soluble initiator and monomer are added to the seed kettle, and then nucleation and polymerization are carried out at a certain temperature to generate latex particles of sufficient size and small size. Then, another monomer (or monomer mixture) is slowly added to partially swell the particles, and then part of the initiator is added to allow the second step of polymerization to be carried out in the outer new monomer phase. After the reaction is completed, the product is separated and dried to obtain the product. Since core-shell polymers are usually prepared by segmented polymerization of two or more monomer molecules with different properties under specific conditions, a series of heterogeneous products with different compositions and forms can be designed according to needs, thereby obtaining products with different functions and properties. Styrene and acrylate polymers are more commonly used in seed emulsion polymerization, such as MBS, which is used as a toughening agent for polyvinyl chloride, that is, butadiene elastomer is used as the core, and methyl methacrylate and styrene are polymerized into the shell.
[0004] In seed emulsion polymerization, if the same monomer is used in the preparation of the seed emulsion and the subsequent polymerization, the result is only the growth of the particles. If a certain monomer is used in the seed polymerization and another monomer is used in the subsequent polymerization, particles with a special core-shell structure are formed. Summary of the invention
[0005] The present invention provides a method for preparing latex, which comprises the following steps:
[0006] 1) obtaining a mixed solution including a first initiator, a first surfactant and a first solvent, optionally adding a first molecular weight regulator, and uniformly adding the seed emulsion monomer to the mixed solution for emulsion polymerization to obtain a seed emulsion;
[0007] 2) Taking the latex particles of the seed emulsion as the core, an emulsion polymerization reaction of the shell structure monomer is carried out to obtain a polymer latex with a core-shell structure.
[0008] According to the present invention, in step 1), the seed emulsion monomer is added at a rate of 1 to 10 g / min. Studies have found that by controlling the addition rate of the seed emulsion monomer, especially controlling it within the above range, ensuring a stable reaction rate and ensuring uniform growth of the colloid particles is conducive to improving the polymerization conversion rate of the seed emulsion monomer.
[0009] Preferably, the uniform addition time is 0.1 to 5 hours, preferably 0.5 to 3 hours.
[0010] According to the present invention, in step 1), the first solvent is selected from water. Studies have found that when water is selected as the first solvent, the surfactant can be well dissolved in the aqueous solution to form micelles with stable structure, thereby ensuring the progress of the polymerization reaction.
[0011] According to the present invention, in step 2), a second surfactant is also introduced into the emulsion polymerization reaction. Studies have found that the introduction of the second surfactant can play an emulsifying role to form an oil-in-water system.
[0012] According to the present invention, in step 2), the emulsion polymerization is carried out in the presence of a second initiator, and the second initiator is added in batches. For example, the second initiator is introduced twice or three times or more. Studies have found that as the reaction proceeds, since the initiator has a half-life, the rate of the polymerization reaction will increase first and then decrease. The purpose of adding the second part of the second initiator in step (3) is to add the second initiator before the second initiator enters the half-life, so that the active second initiator is always present in the polymerization system. Otherwise, if the second initiator is added once, as the amount of shell structure monomer added increases, the activity of the second initiator will also decrease with the reaction time, thereby affecting the conversion rate of the shell structure monomer, and causing the particle size of the core-shell structure polymer to decrease, while causing its mechanical properties to decrease.
[0013] In the method of the present invention, when the total amount of the seed emulsion monomer and the shell structure monomer remains unchanged, the ratio of the seed emulsion monomer is adjusted to prepare polymer latexes with different particle sizes. Specifically, if the ratio of the seed emulsion monomer is increased, a polymer latex with a relatively reduced particle size can be prepared, and conversely, if the ratio of the seed emulsion monomer is reduced, a polymer latex with a relatively increased particle size can be prepared.
[0014] According to the present invention, the conversion rate of the shell structure monomer is greater than 90%, preferably 91-99%, for example 98%.
[0015] According to the present invention, the preparation method further comprises optionally adding a second molecular weight regulator in step (2). Further, the second molecular weight regulator is first mixed with the shell structure monomer and then added to the seed emulsion at a uniform speed, and the uniform addition time can be 1 to 8 hours, preferably 2 to 4 hours.
[0016] According to the present invention, based on the total weight of the monomers in steps (1) and (2), the amount of the first molecular weight regulator is 0.1 to 1% by weight, preferably 0.4 to 0.8% by weight.
[0017] According to the present invention, based on the total weight of the monomers in steps (1) and (2), the amount of the second molecular weight regulator is 0.1 to 1% by weight, preferably 0.3 to 0.6% by weight.
[0018] The present invention also provides a latex prepared by the method, wherein the latex is a polymer latex with a core-shell structure.
[0019] According to the present invention, in the latex particles having a core-shell structure, the particle size of the core part is not greater than 90 nm, for example, 1 to 200 nm, for example, 10 to 100 nm, and specifically 10 to 90 nm.
[0020] According to the present invention, the average particle size of the core-shell structured colloid particles is 70 to 130 nm, specifically 90 to 120 nm.
[0021] According to the present invention, in the core-shell structure, the core includes a first polymer and the shell includes nitrile rubber.
[0022] According to the present invention, the first polymer is selected from at least one of polymethyl methacrylate and polystyrene.
[0023] According to the present invention, the nitrile rubber is selected from at least one of nitrile rubber and carboxylated nitrile rubber. Specifically, the nitrile rubber is acrylonitrile-butadiene rubber. Specifically, the carboxylated nitrile rubber is acrylonitrile-butadiene-acrylic rubber.
[0024] According to the present invention, the latex has at least one of the following properties:
[0025] (1) Solid content greater than 38%, preferably 38-43%, for example 41±2%;
[0026] (2) The viscosity is not greater than 11 mPa.S, preferably 5 to 10 mPa.S, for example, 1 mPa.S, 5 mPa.S, 6 mPa.S, 7 mPa.S, 8 mPa.S, 9 mPa.S, 10 mPa.S;
[0027] (3) Mechanical stability is not more than 6%, preferably 0.1-6%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%;
[0028] (4) The chemical stability is not more than 10%, preferably 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%.
[0029] The present invention also provides application of the latex for preparing or using high-strength oil-resistant products.
[0030] Beneficial effects:
[0031] Through this process, core-shell structure polymers with high conversion rate can be prepared, and the latex state is stable; the particle size distribution of the latex particles is uniform, the viscosity is low, and there is good processing performance; it also has heat resistance and oil resistance; it has excellent physical properties, high strength and high wear resistance.
[0032] The present invention adopts seed emulsion polymerization technology to first prepare seed emulsion and then graft another monomer to form a polymer latex with a core-shell structure. The polymerization method can effectively control the diameter and distribution of latex particles. Under the premise of unchanged monomer amount, increasing the amount of seed emulsion can reduce the particle size; while reducing the amount of seed emulsion can increase the particle size. The core and shell structures influence each other, and the advantages of the two structures complement each other to manufacture polymer latex with special core-shell structure latex particles, giving the polymer latex special functions and excellent performance, especially significantly improved mechanical stability and chemical stability, and excellent physical properties.
[0033] The preparation method of latex provided by the invention can prepare core-shell structure polymer with high conversion rate, and the latex is stable; the latex has uniform particle size distribution, low viscosity, good processing performance, and has both heat resistance and oil resistance. DETAILED DESCRIPTION
[0034] [Preparation method of latex]
[0035] As mentioned above, the present invention provides a method for preparing latex, the method comprising the following steps:
[0036] 1) obtaining a mixed solution including a first initiator, a first surfactant and a first solvent, optionally adding a first molecular weight regulator, and uniformly adding the seed emulsion monomer to the mixed solution for emulsion polymerization to obtain a seed emulsion;
[0037] 2) Taking the latex particles of the seed emulsion as the core, an emulsion polymerization reaction of the shell structure monomer is carried out to obtain a polymer latex with a core-shell structure.
[0038] According to the present invention, in step 1), the seed emulsion monomer is added at a rate of 1 to 10 g / min (preferably 5 g / min).
[0039] According to the present invention, in step 1), the first solvent is selected from water. The reason for selecting water as the first solvent is that it is found that the seed emulsion monomer and the first surfactant can be fully contacted therein. When water is selected as the first solvent, the surfactant can be well dissolved in the aqueous solution to form micelles with stable structure. When the molecular chain grows, the micelles are replenished in time to prevent demulsification, thereby ensuring the progress of the polymerization reaction.
[0040] Preferably, the solvent is deionized water. Preferably, the present invention has no particular limitation on the amount of water used, as long as it is conducive to the polymerization reaction. For example, based on 100 parts by weight of the total weight of the seed emulsion monomer and the shell structure monomer in step (1) and step (2), the amount of water used can be 80 to 320 parts by weight.
[0041] In the present invention, the metal ions in the deionized water are metal ions known in the art, such as Mg 2+ , Ca 2+ , Fe 3+ , Fe 2+ The inventors have found that even treated deionized water can hardly completely avoid the presence of metal ions, and these metal ions can affect the polymerization reaction of the seed emulsion monomers.
[0042] According to the present invention, in step 2), a second surfactant is also introduced into the emulsion polymerization reaction.
[0043] According to the present invention, in step 2), the emulsion polymerization is carried out in the presence of a second initiator, and the second initiator is added in batches. For example, the second initiator is introduced twice or three times or more. Studies have found that as the reaction proceeds, since the initiator has a half-life, the rate of the polymerization reaction will increase first and then decrease. The purpose of adding the second part of the second initiator in step (3) is to add the second initiator before the second initiator enters the half-life, so that the active second initiator is always present in the polymerization system. Otherwise, if the second initiator is added once, as the amount of shell structure monomer added increases, the activity of the second initiator will also decrease with the reaction time, thereby affecting the conversion rate of the shell structure monomer, and causing the particle size of the core-shell structure polymer to decrease, while causing its mechanical properties to decrease.
[0044] According to the present invention, in step (1), the conditions for uniform addition generally include contact temperature and contact time. Preferably, step (1) can be carried out at a relatively low uniform addition temperature, for example, the uniform addition temperature can be 0 to 50°C, preferably 5 to 35°C. Preferably, the inventors have found that extending the uniform addition time is conducive to improving the polymerization conversion rate, but too long a uniform addition time does not significantly improve the conversion rate. Further, the uniform addition time can be 0.1 to 5 hours, preferably 0.5 to 3 hours.
[0045] According to the present invention, the reaction conditions in step (2) are not particularly limited, as long as the core-shell structure polymer latex can be obtained. For example, the reaction conditions generally include the reaction temperature and the reaction time; the reaction temperature is 0 to 50° C., preferably 0 to 10° C., and the reaction time is 0.5 to 5 hours, preferably 1 to 2 hours.
[0046] According to the present invention, the seed emulsion monomers and the shell structure monomers are identical to or different from each other and are selected from monomers containing a double bond structure, preferably vinyl monomers and / or conjugated diene monomers.
[0047] Preferably, the conjugated diene monomer may be selected from at least one of 1,3-butadiene, isoprene, 1-methylbutadiene, 2,3-dimethylbutadiene, piperylene, and chloroprene, preferably butadiene.
[0048] Preferably, the vinyl monomer can be selected from at least one of methyl methacrylate, acrylic acid, methacrylonitrile, styrene, α-methylstyrene, propyl acrylate, butyl acrylate, butyl methacrylate or unsaturated carboxylic acid, preferably at least one of methyl methacrylate, acrylonitrile and styrene.
[0049] Furthermore, the unsaturated carboxylic acid is selected from at least one of acrylic acid and methacrylic acid.
[0050] Exemplarily, the seed emulsion monomer is selected from at least one of methyl methacrylate and styrene.
[0051] Exemplarily, the shell structure monomer is selected from at least one of butadiene, acrylonitrile and acrylic acid.
[0052] Exemplarily, the seed emulsion monomer is selected from methyl methacrylate; the shell structure monomer is selected from a mixture of acrylonitrile and butadiene, and the mass ratio thereof is 300:900; the mass ratio of the seed emulsion monomer to the shell structure monomer is (300-500):1200.
[0053] Exemplarily, the seed emulsion monomer is selected from methyl methacrylate; the shell structure monomer is selected from a mixture of acrylonitrile, butadiene and acrylic acid, and the mass ratio thereof is 250:850:100; the mass ratio of the seed emulsion monomer to the shell structure monomer is (300-500):1200.
[0054] Exemplarily, the seed emulsion monomer is selected from styrene; the shell structure monomer is selected from a mixture of acrylonitrile and butadiene, and the mass ratio thereof is 300:900; the mass ratio of the seed emulsion monomer to the shell structure monomer is (300-500):1200.
[0055] Exemplarily, the seed emulsion monomer is selected from styrene; the shell structure monomer is selected from a mixture of acrylonitrile, butadiene and acrylic acid, and the mass ratio thereof is 250:850:100; the mass ratio of the seed emulsion monomer to the shell structure monomer is (300-500):1200.
[0056] According to the present invention, in step 1), the seed emulsion includes latex particles, and the particle size of the latex particles is not more than 90nm, for example, 10-90nm, and for example, 75nm, 79nm, 85nm. In the present invention, firstly, the seed emulsion monomer dissolved in water, such as, if methyl methacrylate is used for polymerization, then the solubility of methyl methacrylate in water at room temperature is 15.9g / L, and the polymer is insoluble in water. When the polymer chain grows to a critical length, it precipitates from the aqueous phase to form primary ecological particles, that is, the so-called homogeneous nucleation mechanism. Subsequently, methyl methacrylate diffuses into the primary ecological particles and continues to react to form the colloid particles of the seed emulsion. The shell structure monomers in the core-shell structure added subsequently, such as acrylonitrile and butadiene monomers, diffuse into the colloid particles of the seed emulsion for copolymerization, and the colloid particles grow. The electronegativity of the cyano group on the copolymer chain is conducive to enhancing the intermolecular force, and generates electrostatic repulsion between the particles, increasing the distance between the colloid particles, thereby stabilizing the latex. The surfactant is adsorbed on the surface of the latex particles, further enhancing the stability of the latex.
[0057] In the present invention, the amount of the seed emulsion monomer and the shell structure monomer is not particularly limited. Preferably, based on the total weight of the seed emulsion monomer and the shell structure monomer, the amount of the seed emulsion can be 20 to 60% by weight, and the amount of the shell structure monomer can be 20 to 75% by weight. Further preferably, based on the total weight of the seed emulsion monomer and the shell monomer, the amount of the seed emulsion monomer is 25 to 50% by weight, and the amount of the shell structure monomer can be 50 to 75% by weight.
[0058] The inventors of the present invention have found that adding the seed emulsion monomer and the shell structure monomer at a uniform speed can achieve better technical effects. For example, when the seed emulsion monomer is slowly and uniformly added in the preparation of the seed emulsion in step (1), and the shell structure monomer is uniformly added in step (2), the conversion rate of the prepared core-shell structure polymer latex is high and the performance is very excellent.
[0059] Illustratively, the addition is performed at a uniform speed, for example using a feeding pump, the feeding time is controlled within 3 to 6 hours, and the feeding speed is kept constant.
[0060] According to the present invention, based on the total weight of the seed emulsion monomer and the shell structure monomer, the amount of the first initiator is 0.05 to 1% by weight, preferably 0.1 to 0.5% by weight.
[0061] According to the present invention, based on the total weight of the seed emulsion monomer and the shell structure monomer, the amount of the first part of the second initiator is 0.02 to 1% by weight, preferably 0.05 to 0.3% by weight.
[0062] According to the present invention, the amount of the third initiator is 0.01 to 1% by weight, preferably 0.3 to 0.6% by weight, based on the total weight of the seed emulsion monomer and the shell structure monomer. The inventors of the present invention have found that the addition of the third initiator in step (3) can effectively accelerate the reaction speed and improve the conversion rate of the shell structure monomer.
[0063] According to the present invention, the type of the initiator is not particularly limited, as long as it can achieve polymerization of the monomer to obtain the latex.
[0064] Preferably, the first initiator and the second initiator are the same or different from each other and are selected from at least one of potassium persulfate, ammonium persulfate, dialkyl peroxide, azo compound or alkyl peroxide. Further preferably, the initiator is selected from at least one of cumene peroxide, tert-butyl hydroperoxide and benzoyl peroxide.
[0065] Further, the first initiator and the second initiator are different from each other.
[0066] According to the present invention, in order to improve the initiation efficiency of the initiator, a reducing agent may be further added. Preferably, the reducing agent is selected from ferrous sulfate, cuprous sulfate, sodium bisulfite, sodium sulfite, preferably ferrous sulfate.
[0067] According to the present invention, based on the total weight of the seed emulsion monomer and the shell structure monomer, the amount of the first surfactant is 0.1 to 5 weight %, preferably 0.3 to 2 weight %.
[0068] According to the present invention, based on the total weight of the seed emulsion monomer and the shell structure monomer, the amount of the second surfactant is 0.1 to 5% by weight, preferably 0.2 to 1% by weight.
[0069] According to the present invention, the step 2) may specifically include the following steps:
[0070] 2a) taking the seed emulsion obtained in step 1), adding a second surfactant, a part of the second initiator and a mixed solution of a shell structure monomer, and carrying out an emulsion polymerization reaction with the latex particles of the seed emulsion as the core;
[0071] 2b) adding the remaining amount of the second initiator to the reaction mixture obtained in step 2a) and continuing the reaction to prepare a polymer latex having a core-shell structure.
[0072] According to the present invention, in step 2a), the first part of the second initiator and the second surfactant are first added, and then the shell structure monomer is continuously and uniformly added to carry out polymerization reaction.
[0073] Preferably, the shell structure monomer is added for 1 to 8 hours, preferably 3 to 6 hours.
[0074] Preferably, in step 2a), the polymerization reaction temperature is 0 to 50°C, preferably 4 to 35°C.
[0075] Preferably, in step 2a), the polymerization reaction time is 1 to 8 hours, preferably 2 to 4 hours.
[0076] According to the present invention, in step 2b), the reaction conditions include: reaction temperature of 0 to 50° C., preferably 0 to 10° C.; reaction time of 0.5 to 5 hours, preferably 1 to 2 hours.
[0077] According to the present invention, the preparation method further comprises adding a chelating agent in step 2).
[0078] Preferably, the chelating agent can be a chelating agent known in the art, preferably ethylenediaminetetraacetic acid salt. Further, the ethylenediaminetetraacetic acid salt is selected from at least one of ethylenediaminetetraacetic acid disodium salt, ethylenediaminetetraacetic acid trisodium salt, and ethylenediaminetetraacetic acid tetrasodium salt.
[0079] Preferably, based on the total weight of the monomers in step 2a), the amount of the chelating agent is 0.01 to 0.15 wt %, preferably 0.05 to 0.1 wt %.
[0080] The inventors have found that the stability of the polymerization system can be effectively improved by adding a second surfactant in step (2).
[0081] According to the present invention, after the second surfactant is added, the reaction is continued under stirring. Preferably, the reaction time is 0.5 to 5 hours, preferably 1 to 2 hours.
[0082] According to the present invention, the type of the surfactant is not particularly limited, and any surfactant known in the art can be selected.
[0083] Preferably, the first surfactant and the second surfactant are selected from at least one of a cationic surfactant, an anionic surfactant, and a nonionic sub-surfactant, which are the same or different from each other. Exemplarily, the cationic surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate, potassium oleate, and sodium oleate. Exemplarily, the anionic surfactant is selected from at least one of hexadecyl trimethyl ammonium chloride and polyquaternium-16. Exemplarily, the nonionic sub-surfactant is selected from at least one of alkylphenol polyoxyethylene ether and alkyl alcohol amide.
[0084] Illustratively, the first surfactant and the second surfactant are the same as each other.
[0085] Illustratively, the first surfactant and the second surfactant are different from each other.
[0086] According to the present invention, in order to overcome the inhibition of oxygen and obtain a seed latex with a larger molecular weight, preferably, the preparation method is carried out in an inert atmosphere. The inert atmosphere in the present invention refers to any gas or a mixture of gases that do not chemically react with the reactants and reaction products and do not affect the normal reaction of the reactants and reaction products, for example, at least one selected from nitrogen, helium and the zero group gas of the periodic table. The method for maintaining the inert atmosphere is to introduce any gas or gas mixture that does not chemically react with the reactants and products into the polymerization system.
[0087] According to the present invention, the preparation method further comprises optionally adding a second molecular weight regulator in step (2). Further, the second molecular weight regulator is first mixed with the shell structure monomer and then added to the seed emulsion at a uniform speed, and the uniform addition time can be 1 to 8 hours, preferably 2 to 4 hours.
[0088] According to the present invention, based on the total weight of the monomers in steps (1) and (2), the amount of the first molecular weight regulator is 0.1 to 1% by weight, preferably 0.4 to 0.8% by weight.
[0089] According to the present invention, based on the total weight of the monomers in steps (1) and (2), the amount of the second molecular weight regulator is 0.1 to 1% by weight, preferably 0.3 to 0.6% by weight.
[0090] The inventors of the present invention have found that if the monomers are added slowly and uniformly and the initiator is added in batches during the preparation of the seed emulsion, the resulting seed emulsion has better stability; if a certain amount of surfactant is added during the polymerization reaction, it will also significantly help to improve the stability of the colloid particles; in addition, if an initiator is added during the polymerization reaction, the conversion rate of the reaction can be greatly improved.
[0091] According to the present invention, the molecular weight regulator refers to a compound that can control the molecular weight of the polymer and reduce the branching of the polymer chain. Due to its large chain transfer constant, during the polymerization reaction, only a small amount of the molecular weight regulator needs to be added to reduce the molecular weight of the polymer product, which is beneficial to the post-processing and application of the polymer. When the molecular weight of the polymer reaches a certain level, the performance of the polymer material decreases with the increase of the molecular weight. The larger the molecular weight, the higher the melt viscosity, the worse the fluidity, and the more difficult it is to process. Therefore, the molecular weight of the polymer product can also be controlled by adjusting the amount of the molecular weight regulator.
[0092] According to the present invention, the first molecular weight regulator and the second molecular weight regulator can be selected from types and amounts known in the art, for example, the first molecular weight regulator and the second molecular weight regulator are selected from mercaptan molecular weight regulators, which are the same or different from each other. Further, the mercaptan molecular weight regulator is selected from at least one of n-dodecyl mercaptan, tert-dodecyl mercaptan, and octyl mercaptan, and is more preferably tert-dodecyl mercaptan.
[0093] Preferably, the first molecular weight regulator and the second molecular weight regulator are the same.
[0094] Preferably, based on the total amount of the seed emulsion monomer and the shell structure monomer, the amount of the first molecular weight regulator is 0.1 to 1% by weight, preferably 0.4 to 0.8% by weight.
[0095] Preferably, based on the total amount of the seed emulsion monomer and the shell structure monomer, the amount of the second molecular weight regulator is 0.1 to 1% by weight, preferably 0.3 to 0.6% by weight.
[0096] According to the present invention, in step (3), as described above, the inventors of the present invention have found that adding a third initiator to the reaction mixture obtained in step (2) and continuing the reaction can improve the conversion rate of step (2).
[0097] Preferably, the reaction conditions of step (3) may be the same as those of step (2). Preferably, in step (3), after adding the third initiator, the reaction mixture is adjusted to 4-30° C., and the reaction is continued until the polymerization conversion rate of the shell structure monomer is greater than 90%. The inventors of the present invention have found through research that this process usually only takes 0.5-2.5 hours.
[0098] According to the present invention, the conversion rate of the shell structure monomer is greater than 90%, preferably 91-99%, for example 98%.
[0099] [latex]
[0100] The present invention also provides a latex prepared by the preparation method of the present invention, wherein the latex comprises a polymer having a core-shell structure.
[0101] According to the present invention, in the latex, the shell structure of the core-shell structure polymer is selected from a polymer obtained by polymerizing at least one of vinyl monomers and / or conjugated diene monomers.
[0102] According to the present invention, in the latex, the core structure of the core-shell structure polymer is selected from a polymer obtained by polymerizing at least one of vinyl monomers and / or conjugated diene monomers.
[0103] According to the present invention, the conjugated diene monomer and the vinyl monomer have the meanings as described above.
[0104] Exemplarily, the core structure is selected from a first polymer. Further, the first polymer is selected from at least one of polymethyl methacrylate and polystyrene.
[0105] Exemplarily, the core structure is selected from nitrile rubber. Further, the nitrile rubber is selected from at least one of nitrile rubber and carboxyl nitrile rubber.
[0106] Furthermore, the nitrile rubber is obtained by polymerization of acrylonitrile and butadiene.
[0107] Furthermore, the carboxylated nitrile rubber is obtained by polymerization of acrylonitrile, butadiene and acrylic acid.
[0108] According to the present invention, in the latex, the average particle size of the core structure of the core-shell structure polymer is 1 to 200 nm, preferably 50 to 100 nm, for example, 75 nm, 79 nm, or 85 nm.
[0109] According to the present invention, the average particle size of the core-shell structure polymer is 70 to 130 nm, preferably 90 to 120 nm.
[0110] According to the present invention, the latex has good mechanical stability and chemical stability.
[0111] Preferably, the latex has at least one of the following properties:
[0112] (1) Solid content greater than 38%, preferably 38-43%, for example 41±2%;
[0113] (2) The viscosity is not greater than 11 mPa.S, preferably 5 to 10 mPa.S, for example, 1 mPa.S, 5 mPa.S, 6 mPa.S, 7 mPa.S, 8 mPa.S, 9 mPa.S, 10 mPa.S;
[0114] (3) Mechanical stability is not more than 6%, preferably 0.1-6%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%;
[0115] (4) The chemical stability is not more than 10%, preferably 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%.
[0116] In the present invention, the mechanical stability refers to the stability of the latex after rotating at a speed higher than 10,000 rpm (eg, 14,000 rpm) for 30 minutes, and the chemical stability refers to the stability of the latex to calcium ions.
[0117] [application]
[0118] The present invention also provides application of the latex, for example, application in high-strength oil-resistant products.
[0119] According to an embodiment of the present invention, the high-strength oil-resistant product is, for example, an oil-resistant gasket, a gasket, a cable hose, a sealing ring, and the like.
[0120] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0121] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0122] The particle sizes in the following examples were measured using a laser particle size analyzer (manufacturer: Malvern Panalytical). The overall structure of the core and shell polymers was observed using a transmission electron microscope. The polymerization experiments were conducted using an American PARR high-pressure reactor.
[0123] Example 1
[0124] (1) Preparation of seed emulsion:
[0125] 2000g of deionized water, 2g of sodium dodecylbenzene sulfonate and 3g of sodium dodecyl sulfate are added to a 7L polymerization kettle in sequence, and stirring and mixing are started. Vacuuming and nitrogen filling are performed for replacement three times, and then the temperature is lowered to 15°C, 1.5g of isopropyl peroxide and 1.8g of tert-dodecyl mercaptan are added, and then 300g of methyl methacrylate is uniformly added to the polymerization kettle as a seed emulsion monomer, and the addition time is 1h (i.e., the dropwise addition rate of the seed emulsion monomer methyl methacrylate is about 5g / min); the reaction is carried out at a constant temperature of 15°C for 2 hours to prepare a seed emulsion with an average diameter of about 83nm of colloid particles, and the conversion rate of the seed emulsion is 98%, wherein the particle size distribution of the colloid particles is uniform, and the colloid particles constitute a core structure.
[0126] (2) Preparation of emulsion with core-shell polymer:
[0127] The seed emulsion obtained in step (1) is cooled to 10° C., 0.03 g of trisodium ethylenediaminetetraacetic acid, 6 g of tert-dodecyl mercaptan, 3 g of sodium dodecyl sulfate, 6 g of sodium dodecylbenzene sulfonate, 1 g of isopropylbenzene peroxide and 1.5 g of ferrous sulfate are added, and a uniform mixture consisting of 300 g of acrylonitrile and 900 g of butadiene is added at a uniform rate over 3.5 hours, and the mixture is reacted for 3 hours to generate a shell structure outside the core structure.
[0128] (3) 2.5 g of cumene peroxide was further added and the reaction was continued for 2 hours to make the conversion rate of the above shell structure monomer reach 98%, thereby obtaining a latex having a core-shell structure polymer, wherein the average particle size of the core-shell structure polymer was about 105 nm.
[0129] Example 2
[0130] (1) Preparation of seed emulsion:
[0131] 2000g of deionized water, 2g of sodium dodecylbenzene sulfonate and 3g of sodium dodecyl sulfate were added to a 7L polymerization kettle in sequence, and stirring and mixing were started. Vacuuming and nitrogen filling were performed three times, and then the temperature was lowered to 15°C, 1.5g of isopropyl peroxide and 1.8g of tert-dodecyl mercaptan were added, and then 300g of methyl methacrylate was uniformly added to the polymerization kettle as a seed emulsion monomer, and the addition time was 1h (i.e., the dropwise addition rate of the seed emulsion monomer methyl methacrylate was about 5g / min); the reaction was carried out at a constant temperature of 15°C for 2 hours to prepare a seed emulsion with an average diameter of colloid particles of about 83nm, and the conversion rate of the seed emulsion was 98%.
[0132] (2) Preparation of latex with core-shell polymer:
[0133] The seed emulsion obtained in step (1) is cooled to 10°C, 0.03g of trisodium ethylenediaminetetraacetic acid, 6g of tert-dodecyl mercaptan, 3g of sodium dodecyl sulfate, 6g of sodium dodecylbenzene sulfonate, 1g of isopropylbenzene peroxide and 1.5g of ferrous sulfate are added, and a uniform mixture consisting of 250g of acrylonitrile, 850g of butadiene and 100g of acrylic acid is continuously added within 6 hours, and the reaction is continued for 3 hours.
[0134] (3) 2.5 g of cumene peroxide was added and the reaction was continued for 2 hours to make the conversion rate of the shell structure monomer reach 98%, thereby obtaining a latex having a core-shell structure polymer, wherein the particle size of the core-shell structure polymer was 109 nm.
[0135] Example 3
[0136] (1) Preparation of seed emulsion:
[0137] 2000g of deionized water, 2g of sodium dodecylbenzene sulfonate, 2g of sodium octadecyl sulfate and 1g of sodium stearate are added to a 7L polymerization kettle in sequence, and stirring and mixing are started. Vacuuming and nitrogen filling are performed three times, and then the temperature is lowered to 15°C, 1.2g of tert-butyl hydroperoxide and 1.5g of tert-dodecyl mercaptan are added, and then 300g of styrene is uniformly added to the polymerization kettle as a seed emulsion monomer, and the addition time is 1h (that is, the dropwise addition rate of the seed emulsion monomer styrene is about 5g / min); the reaction is carried out at this temperature for 3 hours to prepare a seed emulsion with an average diameter of colloid particles of about 79nm, and the conversion rate of the seed emulsion is 98%.
[0138] (2) Preparation of latex with core-shell polymer:
[0139] The seed emulsion obtained in step (1) is cooled to 10° C., 0.03 g of ethylenediaminetetraacetic acid, 6 g of tert-dodecyl mercaptan, 3 g of sodium dodecyl sulfate, 6 g of sodium dodecylbenzene sulfonate, 1 g of tert-butyl hydroperoxide and 1.5 g of ferrous sulfate are added, and a uniform mixture consisting of 300 g of acrylonitrile and 900 g of butadiene is continuously added within 6 hours, and the reaction is continued for 3 hours.
[0140] (3) 2.5 g of tert-butyl hydroperoxide was added and the reaction was continued for 2 hours to make the conversion rate of the shell structure monomer reach 98%, thereby obtaining a latex having a core-shell structure polymer, wherein the particle size of the core-shell structure polymer was 95 nm.
[0141] Example 4
[0142] (1) Preparation of seed emulsion:
[0143] 2000g of deionized water, 2g of sodium dodecylbenzene sulfonate, 2g of sodium dodecyl sulfate and 1g of sodium stearate were added to a 7L polymerization kettle in sequence, and stirring and mixing were started. Vacuuming and nitrogen filling were performed for replacement three times, and then the temperature was lowered to 10°C, 1.2g of tert-butyl hydroperoxide and 1.5g of tert-dodecyl mercaptan were added, and then 300g of styrene was uniformly added to the polymerization kettle as a seed emulsion monomer, and the addition time was 1h (that is, the dropwise addition rate of the seed emulsion monomer methyl methacrylate was about 5g / min); the reaction was carried out at this temperature for 3 hours to prepare a seed emulsion with an average diameter of colloid particles of about 79nm, and the seed emulsion conversion rate was 98%.
[0144] (2) Preparation of latex with core-shell polymer:
[0145] The seed emulsion obtained in step (1) is cooled to 10° C., 0.03 g of trisodium ethylenediaminetetraacetic acid, 6 g of tert-dodecyl mercaptan, 3 g of sodium dodecyl sulfate, 6 g of sodium dodecylbenzene sulfonate, 1 g of tert-butyl hydroperoxide and 1.5 g of ferrous sulfate are added, and a uniform mixture consisting of 250 g of acrylonitrile, 850 g of butadiene and 100 g of acrylic acid is continuously added within 6 hours, and the reaction is continued for 3 hours.
[0146] (3) 2.5 g of tert-butyl hydroperoxide was added and the reaction was continued for 2 hours to make the conversion rate of the shell structure monomer reach 98%, thereby obtaining a latex having a core-shell structure polymer, wherein the particle size of the core-shell structure polymer was 106 nm.
[0147] Example 5
[0148] A latex having a core-shell structure polymer was prepared according to the method of Example 1, except that the amount of methyl methacrylate added in step (1) was 500 g, the amount of acrylonitrile added in step (2) was 300 g, and the amount of butadiene was 600 g, that is, the proportion of the monomer in the seed emulsion was increased.
[0149] In step (1), the conversion rate of the obtained seed emulsion is 98%, and the average diameter of the colloid particles is 84nm; in step (2), the conversion rate of the shell structure monomer is 98%, and the particle size of the core-shell structure polymer is 108nm.
[0150] Example 6
[0151] A latex having a core-shell structure polymer was prepared according to the method of Example 1, except that the amount of sodium dodecylbenzene sulfonate added in step (1) was 1 g, and the amount of sodium dodecyl sulfate was 1.5 g; the amount of sodium dodecyl sulfate added in step (2) was 1.5 g, and the amount of sodium dodecylbenzene sulfonate was 3 g, that is, the amount of surfactant used was reduced.
[0152] In step (1), the conversion rate of the obtained seed emulsion is 94%, and the average diameter of the colloid particles is 76nm; in step (2), the conversion rate of the shell structure monomer is 92%, and the particle size of the core-shell structure polymer is 93nm.
[0153] Example 7
[0154] A latex having a core-shell structure polymer was prepared according to the method of Example 1, except that the amount of cumene peroxide added in step (1) was 2 g, and the amount of cumene peroxide added in step (2) was 1.5 g, i.e., the amount of initiator cumene peroxide was increased.
[0155] In step (1), the conversion rate of the obtained seed emulsion is 96%, and the average diameter of the colloid particles is 78nm; in step (2), the conversion rate of the shell structure monomer is 94%, and the particle size of the core-shell structure polymer is 96nm.
[0156] Example 8
[0157] A latex having a core-shell structure polymer was prepared according to the method of Example 3, except that the amount of styrene added in step (1) was 500 g, and the amount of acrylonitrile added in step (2) was 200 g and the amount of butadiene was 700 g, that is, the proportion of the seed emulsion monomer was increased.
[0158] In step (1), the conversion rate of the obtained seed emulsion is 98%, and the average diameter of the colloid particles is 80nm; in step (2), the conversion rate of the shell structure monomer is 98%, and the particle size of the core-shell structure polymer is 104nm.
[0159] Example 9
[0160] A latex having a core-shell structure polymer was prepared according to the method of Example 3, except that the amount of sodium dodecylbenzene sulfonate added in step (1) was 1 g, the amount of sodium dodecyl sulfate was 1 g, and the amount of sodium stearate was 0.5 g; the amount of sodium dodecyl sulfate added in step (2) was 1.5 g, and the amount of sodium dodecylbenzene sulfonate was 3 g, that is, the amounts of surfactants sodium dodecyl sulfate and sodium dodecylbenzene sulfonate were reduced.
[0161] In step (1), the conversion rate of the obtained seed emulsion is 93%, and the average diameter of the colloid particles is 70nm; in step (2), the conversion rate of the shell structure monomer is 92%, and the particle size of the core-shell structure polymer is 88nm.
[0162] Example 10
[0163] A latex having a core-shell structure polymer was prepared according to the method of Example 3, except that the amount of tert-butyl hydroperoxide added in step (1) was 2 g, and the amount of tert-butyl hydroperoxide added in step (2) was 1.5 g, that is, the amount of initiator tert-butyl hydroperoxide was increased.
[0164] In step (1), the conversion rate of the obtained seed emulsion is 94%, and the average diameter of the colloid particles is 72nm; in step (2), the conversion rate of the shell structure monomer is 93%, and the particle size of the core-shell structure polymer is 90nm.
[0165] Comparative Example 1
[0166] 2000g of deionized water, 3g of sodium dodecyl sulfate, 6g of sodium dodecylbenzene sulfonate, 0.04 of trisodium ethylenediaminetetraacetic acid, and 1.5g of ferrous sulfate were sequentially added into a 7L polymerization kettle, and stirred and mixed evenly, and vacuumed and nitrogen-filled for replacement three times, and then cooled to 10°C, and a uniform mixture of monomers consisting of 1g of cumene peroxide and 6g of tert-dodecyl mercaptan, 300g of acrylonitrile and 900g of butadiene was added, and added continuously within 6 hours, and then 1.5g of cumene peroxide was added and the temperature was cooled to 5°C and the reaction was continued for 3 hours to obtain a pure butadiene latex without a core-shell structure. The conversion rate of the mixture monomers reached 98%, wherein the particle size of the polymer was 60-80nm, and the average particle size was about 70nm.
[0167] Comparative Example 2
[0168] The latex of the core-shell structure polymer was prepared according to the method of Example 1, except that 3.5 g of cumene peroxide initiator was added at one time in step (2). The latex of the core-shell structure polymer was obtained, and the conversion rate of the shell structure monomer reached 95%, wherein the particle size of the core-shell structure polymer was 98 nm, and its mechanical properties were also reduced accordingly.
[0169] Comparative Example 3
[0170] A latex having a core-shell structure polymer was prepared according to the method of Example 1, except that 14 g of surfactant was added in step (1) and no surfactant was added in step (2).
[0171] In this comparative example, due to the addition of excessive surfactant in step (1), the seed emulsion will demulsify, the conversion rate of the shell structure is reduced to 87%, and the particle size is reduced. After step (1), the particle size in the seed emulsion is about 75 nm.
[0172] At the same time, demulsification also occurred after the polymerization reaction in step (3) was completed. The inventors believed that this was caused by excessive consumption of surfactant in step (1). The particle size of the polymer finally obtained in step (3) was about 90 nm, and the mechanical properties of the polymer were also greatly reduced.
[0173] Comparative Example 4
[0174] The latex of the core-shell polymer was prepared according to the method of Example 3, except that no tert-butyl hydroperoxide initiator was added in step (2). The latex of the core-shell polymer was obtained, and the conversion rate of the shell structure monomer reached 92%, wherein the particle size of the core-shell polymer was about 88 nm.
[0175] Comparative Example 5
[0176] A latex having a core-shell structure polymer was prepared according to the method of Example 1, except that the core structure monomers were all added within 3 minutes, and the shell structure monomers were all added within 10 minutes.
[0177] In this comparative example, due to the too fast addition of monomers, demulsification occurred, and the particle size of the seed emulsion was about 82nm; the particle size of the core-shell structure latex was about 97nm; and the conversion rate of the core structure monomer was only 94%. It can be seen that the particle size of the polymer decreased when the monomers were added too quickly.
[0178] Comparative Example 6
[0179] A latex without a core-shell structure was prepared according to the method of Example 1(2) and (3), except that no seed latex was added.
[0180] (1) Prepare 1500 g of deionized water, add 0.03 g of trisodium ethylenediaminetetraacetic acid, 6 g of tert-dodecyl mercaptan, 3 g of sodium dodecyl sulfate, 6 g of sodium dodecylbenzene sulfonate, 1 g of cumene peroxide and 1.5 g of ferrous sulfate, and add a uniform mixture consisting of 300 g of acrylonitrile and 900 g of butadiene at a uniform rate over 3.5 hours, and react for 3 hours.
[0181] (2) 2.5 g of cumene peroxide was further added and the reaction was continued for 2 hours to make the conversion rate of the above monomers reach 98%, thereby obtaining a latex of a core-shell structure polymer, wherein the average particle size of the core-shell structure polymer was about 83 nm.
[0182] Comparative Example 7
[0183] A latex without a core-shell structure was prepared according to the method of Example 2(2) and (3), except that no seed latex was added.
[0184] (1) Prepare 1500 g of deionized water, add 0.03 g of trisodium ethylenediaminetetraacetic acid, 6 g of tert-dodecyl mercaptan, 3 g of sodium dodecyl sulfate, 6 g of sodium dodecylbenzene sulfonate, 1 g of cumene peroxide and 1.5 g of ferrous sulfate, and add a uniform mixture consisting of 250 g of acrylonitrile, 850 g of butadiene and 100 g of acrylic acid continuously within 6 hours, and continue the reaction for 3 hours.
[0185] (2) 2.5 g of cumene peroxide was further added and the reaction was continued for 2 hours to make the conversion rate of the above monomers reach 98%, thereby obtaining a latex of a core-shell structure polymer, wherein the average particle size of the core-shell structure polymer was about 89 nm.
[0186] Test Case
[0187] The latexes of the core-shell structure polymers prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were subjected to performance tests according to the following methods. The test results are shown in Table 1.
[0188] (1) Solid content test:
[0189] The results are shown in Table 1.
[0190] (2) Viscosity test:
[0191] The results are shown in Table 1.
[0192] (3) Mechanical stability test:
[0193] The mechanical stability of the latex with core-shell structure polymer was tested by using a latex mechanical stability tester (purchased from Guangzhou Easy Test Instrument Co., Ltd., model Klaxon). The specific test method is as follows: weigh 50 grams of latex (without water removal), put it into a standard container, rotate the rotor in the latex at a speed of 14,000 rpm for 30 minutes, filter, and determine its flocculant content (i.e., the content of the filter residue). The mechanical stability of the latex with core-shell structure polymer is calculated according to the following formula: S = Ws1 / Ws×100%, S is the percentage of flocculants, Ws1 is the weight of mechanical flocculants; Ws is the weight of the latex to be tested. The smaller S is, the better the mechanical stability performance is. The results are shown in Table 1.
[0194] (4) Chemical stability test:
[0195] Chemical stability of latex with core-shell polymer was investigated by the latex's irradiation with Ca 2+The chemical stability of latex is characterized by the stability of ions. The specific test method is as follows: add 5g of CaCl2 solution (CaCl2 concentration is 2% by weight) to 50g of latex (without water removal), shake well and let it stand for 2 hours, filter and measure its flocculant content (i.e. the content of filter residue). The chemical stability of latex is calculated according to the following formula: C = Wc1 / Wc×100%, C is the percentage of flocculant content; Wc1 is the weight of chemical flocculant; Wc is the weight of latex to be tested. The smaller C is, the better the chemical stability is. The results are shown in Table 1.
[0196] Table 1
[0197]
[0198]
[0199] As can be seen from the results in Table 1, the mechanical stability and chemical stability of the latex with core-shell structure polymer prepared according to the method of the present invention have obvious advantages over the same molecular chain structure polymer without core-shell structure. For example, the mechanical stability of PMMA / NBR latex is obviously better than that of ordinary nitrile rubber.
[0200] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing latex, characterized in that: The preparation method comprises the following steps: 1) obtaining a mixed solution including a first initiator, a first surfactant and a first solvent, optionally adding a first molecular weight regulator, and uniformly adding the seed emulsion monomer to the mixed solution for emulsion polymerization to obtain a seed emulsion; 2) Taking the latex particles of the seed emulsion as the core, an emulsion polymerization reaction of the shell structure monomer is carried out to obtain a polymer latex with a core-shell structure.
2. The preparation method according to claim 1, characterized in that: In step 1), the seed emulsion monomer is added at a rate of 1 to 10 g / min. Preferably, the uniform addition time is 0.1 to 5 hours. Preferably, in step 1), the first solvent is selected from water.
3. The preparation method according to claim 1 or 2, characterized in that: In step 2), a second surfactant is also introduced into the emulsion polymerization reaction. Preferably, in step 2), the emulsion polymerization reaction is carried out in the presence of a second initiator, and the second initiator is added in batches.
4. The preparation method according to any one of claims 1 to 3, characterized in that The conversion rate of the shell structure monomer is greater than 90%. Preferably, the preparation method further comprises optionally adding a second molecular weight regulator in step (2). Further, the second molecular weight regulator is first mixed with the shell structure monomer and then added to the seed emulsion at a uniform speed, and the uniform addition time can be 1 to 8 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Based on the total weight of the monomers in steps (1) and (2), the amount of the first molecular weight regulator is 0.1 to 1% by weight. Preferably, based on the total weight of the monomers in steps (1) and (2), the amount of the second molecular weight regulator is 0.1 to 1% by weight.
6. The latex prepared by the preparation method according to any one of claims 1 to 5, wherein the latex is a polymer latex with a core-shell structure.
7. The latex according to claim 6, characterized in that In the latex particles with a core-shell structure, the particle size of the core part is no greater than 90 nm. Preferably, the average particle size of the core-shell structured colloid particles is 70 to 130 nm.
8. The latex according to claim 6 or 7, characterized in that In the core-shell structure, the core includes a first polymer and the shell includes nitrile rubber. Preferably, the first polymer is selected from at least one of polymethyl methacrylate and polystyrene. Preferably, the nitrile rubber is selected from at least one of nitrile rubber and carboxyl nitrile rubber.
9. The latex according to any one of claims 6 to 8, characterized in that The latex has at least one of the following properties: (1) Solid content greater than 38%; (2) Viscosity not greater than 11 mPa.S; (3) Mechanical stability is not more than 6%; (4) Chemical stability is not more than 10%.
10. Use of the latex according to any one of claims 6 to 9 for preparing or as high-strength oil-resistant products.
Citation Information
Patent Citations
An improved holder for menu cards and for like purposes
GB295882A
Core-shell styrene-butadiene redispersible latex powder
CN107674217A
Core-shell emulsion and preparation method thereof
CN110551245A
Method for improving grafting efficiency of PBA-g-MMA graft copolymer
CN111205399A
Core-shell latex with non-yellowing properties
WO2020170272A1